Pathogenic potential of interferon αβ in acute influenza infection - Davidson, Sophia (Nature Pub. Group, 2014)
Influenza symptoms vary from mild disease to death; however, determinants of severity are unclear. Type I interferons (IFNαβ) are recognized as key antiviral cytokines. Here we show that, surprisingly, influenza-infected 129 mice have increased lung damage, morbidity and mortality, yet higher levels of IFNαβ, than C57BL/6 mice. Consistently, IFNα treatment of influenza-infected C57BL/6 mice increases morbidity. IFNαβ receptor deficiency in 129 mice decreases morbidity, lung damage, proinflammatory cytokines and lung-infiltrating inflammatory cells, and reduces expression of the death-inducing receptor DR5 on lung epithelia and its ligand TRAIL on inflammatory monocytes. Depletion of PDCA-1+ cells or interruption of TRAIL-DR5 interaction protects infected 129 mice. Selective lack of IFNαβ signalling in stromal cells abolishes epithelial DR5 upregulation and apoptosis, reducing host susceptibility. Hence, excessive IFNαβ signalling in response to acute influenza infection can result in uncontrolled inflammation and TRAIL-DR5-mediated epithelial cell death, which may explain morbidity and has important implications for treatment of severe disease.